Mechanical Durability and Grindability of Pellets after Torrefaction Process - Arkadiusz Dyjakon; Tomasz Noszczyk; Agata Mostek (Energies, 2021)
Renewable energy sources and their part in the global energy mix are beneficial to energy diversification and environment protection. However, raw biomass is characterized by low heating value, hydrophilic properties, various mechanical durability, and the logistic challenges related to transportation and storage. One frequently used process of combined biomass valorization is torrefaction and pelletization, which increase the heating value, homogeneity, and hydrophobicity of the fuel. However, industrial clients need fuel characterized by favorable grindability, whereas, the individual clients (householders) need fuel with high mechanical durability. Due to the different expectations of final customers regarding biomass fuel properties, it is necessary to investigate the influence of the torrefaction on the mechanical durability of the pellets. In this paper, five various types of pellets and their torreficates (obtained at a temperature of 200 and 300 °C) were examined. Then the mechanical durability index DU and the grindability of the untreated and torrefied pellets were determined. The results indicated that the mechanical durability of untorrefied pellets is significantly greater than torrefied pellets. Interestingly, no significant differences in mechanical durability between torrefied pellets at 200 and 300 °C were observed, For sunflower husk pellets, the DU index amounted to 95.28 ± 0.72 (untorrefied), 47.22% ± 0.28% (torrefied at 200 °C), and 46.34% ± 0.72% (torrefied at 300 °C). Considering the grindability, as the treatment temperature increased the energy demand for grindability decreased. For example, the grindability of pine tree pellets was 15.96 ± 3.07 Wh·kg−1 (untreated), 1.86 ± 0.31 Wh·kg−1 (torrefied at 200 °C), and 0.99 ± 0.17 Wh·kg−1 (torrefied at 300 °C). The highest difference between raw and torrefied pellets was determined for beetroot pomace pellet: 36.31 ± 2.06 Wh·kg−1 (untreated), 3.85 ± 0.47 Wh·kg−1 (torrefied at 200 °C), and 1.03 ± 0.12 Wh·kg−1 (torrefied at 300 °C).